(untitled) (Research, Society and Development, 2022)
The placement of immediate implants after tooth extraction is a relatively recent technique, which emerged with the purpose of reducing treatment time and the need to preserve alveolar structures destined for atrophy. The objective of the article is to demonstrate the effectiveness of immediate implants, their advantages, disadvantages, criteria for performing the immediate implant, types of grafts and the most used. The referent work is a literature review using Google Scholar, Pubmed, Scielo, with dates from 2005 to 2022. The success rate of this treatment is high when it meets its main characteristics: no infectious process, ideal bone structure and patient follow-up post surgery. Therefore, implants with immediate loading together with bone grafts, if necessary, have good results when observing their detailed anamnesis, criteria for the technique, its advantages, disadvantages for the patient, being essential the orientation and return of the same in order to avoid treatment failure.